Genetic diversity of bread wheat (Triticum aestivum L.) in the allelic composition of HMW-GS (a review) - M. V. Chebatareva (Труды по прикладной ботанике, генетике и селекции)
Background. The qualitative composition of wheat grain varies depending on the cultivar, soil and climate conditions, and agricultural practices. The allelic composition of glutenins in bread wheat cultivars is an important parameter for the analysis and management of their genetic structure. In this respect, there is an interest in studying the genetic diversity of alleles of high-molecular-weight glutenin subunits (HMW-GS) in bread wheat cultivars from Europe, Asia, Africa, and America.Materials and methods. The total diversity of alleles in Glu-1 glutenin loci was evaluated according to the calculation of the Nei index (H). Using this indicator and the cluster analysis, wheat cultivars of various ecogeographic origin were distributed into relatively homogeneous groups.Results. Wheat cultivars from Poland, Germany, France, Spain, Portugal, Turkey, Iran, Pakistan, India, China, and Algeria (Group I) had the average Nei index of 0.59, and those from the U.S., Mexico, Argentina, Russia, Kazakhstan, Ethiopia, Czech Republic, Hungary, Bulgaria, Afghanistan, and North Korea (Group II) had 0.42. These groups of wheat cultivars differed in the frequency of occurrence of glutenin subunits at each Glu-1 locus: N, 7+9, 2+12 in Group I, and 2*, 7+9, 5+10 in Group II.Conclusion. Wheat cultivars from Group II had on average a low level of variability of allelic genes in the respective loci, manifesting high grain quality of these cultivars and the highest probability of their genetic depletion compared to the cultivars from Group I, where most of the cultivars are described by a combination of low-quality glutenin subunits.